The role of social capital in shaping Europeans' immigration sentiments - Claire Economidou; Dimitris Karamanis; Alexandra Kechrinioti; Sofia Xesfingi (IZA Journal of Development and Migration, 2020)
Migration has manifested itself to historic highs, creating divisive views among politicians, policy makers, and individuals. The present paper studies the Europeans' attitudes toward immigration, focusing particularly on the role of social capital. Based on 267,282 respondents from 22 countries and over the period 2002-2014, we find that despite the eventful past years, Europeans, on average, are positive toward immigrants with the North European countries to be the least xenophobic. A salient finding of our analysis is that regardless of the impact of other contextual factors, namely, a country's macroeconomic conditions, ethnic diversity, cultural origin, and individuals' attributes, social capital associates with positive attitudes toward all immigrants, independent of their background. Furthermore, social capital moderates the negative effects of perceived threat on people's opinions about immigrants.
Keywords: C25; F22; J61; O52; 330; immigration; social capital; public attitude; survey; Europe